Design of Phase-Shifting Transformer Based on Simulink Matlab Simulation - Kastawan, I Made Wiwit; Yusuf, Ewin; Fadhilah, Afif (Bandung State Polytechnic (Politeknik Negeri Bandung), 2020)
Using variable speed drive for controlling speed of three-phase induction motor in industrial sector gives an advantage of reducing consumption of electrical energy; on the other hand, it also causes a disadvantage of source current harmonic. To solve the problem of source current harmonic, a method of using phase-shifting transformer is applied. This method may be applied in a system with two VSDs or more connected to a three-phase power supply. The application of this phase-shifting transformer method could be as simple as using of two transformer with Y-y (wye-wye) and Y-d (wye-delta) three-phase winding connections to give a phase-shifting of 30 or more complex as it uses two transformer with Y-y and Y-z (wye-zigzag) three-phase winding connections to give a phase-shifting less than 30. This paper proposes design of five different phase-shifting transformer configurations to produce 30, 20, 15, 12 and 10 phase-shifting. Simulation on a computer-based software, Simulink Matlab, then confirmed that the proposed phase-shifting transformer design gives a very accurate result regarding to phase-shifting and magnitudes of input and output voltage of the phase-shifting transformers.